2009
DOI: 10.1371/journal.ppat.1000348
|View full text |Cite
|
Sign up to set email alerts
|

Bim and Bmf Synergize To Induce Apoptosis in Neisseria Gonorrhoeae Infection

Abstract: Bcl-2 family proteins including the pro-apoptotic BH3-only proteins are central regulators of apoptotic cell death. Here we show by a focused siRNA miniscreen that the synergistic action of the BH3-only proteins Bim and Bmf is required for apoptosis induced by infection with Neisseria gonorrhoeae (Ngo). While Bim and Bmf were associated with the cytoskeleton of healthy cells, they both were released upon Ngo infection. Loss of Bim and Bmf from the cytoskeleton fraction required the activation of Jun-N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
3
27
1
Order By: Relevance
“…The reasons for the discrepancy are not clear but may be related to the use of different N. gonorrhoeae strains or differences in bacterial piliation and/or expression of opacity proteins. Our results also contrast with data demonstrating a proapoptotic effect of N. gonorrhoeae infection on epithelial cells (39,40,50,51), but those discrepancies may reflect the vast differences between PMNs and epithelial cells.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The reasons for the discrepancy are not clear but may be related to the use of different N. gonorrhoeae strains or differences in bacterial piliation and/or expression of opacity proteins. Our results also contrast with data demonstrating a proapoptotic effect of N. gonorrhoeae infection on epithelial cells (39,40,50,51), but those discrepancies may reflect the vast differences between PMNs and epithelial cells.…”
Section: Discussioncontrasting
confidence: 99%
“…We also show that PMNs can be a significant source of proinflammatory cytokines and chemokines during infection, in addition to the epithelial cells which are thought to be responsible for initial PMN recruitment. Numerous studies of epithelial cells and lymphocytes have shown both pro-and antiapoptotic effects of infection with both N. gonorrhoeae (6,27,36,39,40,50,51) and the closely related N. meningitidis (17,48). However, PMN apoptosis during N. gonorrhoeae infection has not been examined as extensively (68), and it has not been explored at all with N. meningitidis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bim and Bmf are associated with the cytoskeleton and are released in a Rac-1-dependent manner after gonococcal infection. 83 …”
Section: Rho Gtpases At Other Stages Of Gonococcal Infectionmentioning
confidence: 99%
“…The activation of three major mitogen activated protein kinases (MAPK), including extracellular signal-regulated kinase (ERK), p38 and c-Jun N-terminal kinase (JNK), has been implicated in the regulation of apoptosis by N. gonorrhoeae [7,8,11] in various cell types. JNK activation was proapoptotic in HeLa cells infected with N. gonorrhoeae [8].…”
Section: Introductionmentioning
confidence: 99%